Postnatal Craniofacial Skeletal Development of Female C57BL/6NCrl Mice - Wei, Xiaoxi; Thomas, Neil; Hatch, Nan E.; Hu, Min; Liu, Fei (Frontiers in Physiology, 2017)
The craniofacial skeleton is a complex and unique structure. The perturbation of its development can lead to craniofacial dysmorphology and associated morbidities. Our ability to prevent or mitigate craniofacial skeletal anomalies is at least partly dependent on our understanding of the unique physiological development of the craniofacial skeleton. Mouse models are critical tools for the study of craniofacial developmental abnormalities. However, there is a lack of detailed normative data of mouse craniofacial skeletal development in the literature. In this report, we employed high-resolution micro-computed tomography (μCT) in combination with morphometric measurements to analyze the postnatal craniofacial skeletal development from day 7 (P7) through day 390 (P390) of female C57BL/6NCrl mice, a widely used mouse strain. Our data demonstrates a unique craniofacial skeletal development pattern in female C57BL/6NCrl mice, and differentiates the early vs. late craniofacial growth patterns. Additionally, our data documents the complex and differential changes in bone parameters (thickness, bone volume, bone volume/tissue volume, bone mineral density and tissue mineral density) of various craniofacial bones with different embryonic origins and ossification mechanisms during postnatal growth, which underscores the complexity of craniofacial bone development and provides a reference standard for future quantitative analysis of craniofacial bones.